Securitisation in South Africa: 2000-2007 - Z. Moyo; C. Firer (South African Journal of Business Management, 2008)
This paper tracks the development of the securitisation market in South Africa since the first securitisation in 1989. It gives a chronological account of securitisation issuance activity on the Bond Exchange of South Africa and identifies factors that have led to the development of the market. It also records some of the topical Issues market participants face.Listing data from the Bond Exchange of South Africa was sorted and analysed. The views of market participants were captured through interviews and by attendance of the 2007 annual securitisation conference.The results show that the South African securitisation market has grown exponentially over the last seven years. Market participants expect this market to continue to grow, but at a slower pace, given the pressure that world credit markets are under as a result of the sub-prime crisis in the US. Market participants identified the constraints to growth as being insufficient capacity of local investors to take up the paper. From a supply point of view the South African banks have substantial securitisation capacity that is still untapped.
Keywords: 650